Strategi Efektif Dalam Mengajarkan Pendidikan Kewarganegaraan Di Sekolah Dasar - Nessa Indahyani (Educational Journal, 2026)
This study aims to identify the role of the subject of Civic Education (PKn) in shaping the character of Civic Education in Elementary Schools has a very important role for students, namely in shaping character, national values, and awareness of the rights and obligations of citizens. However, the dominant Civic Education teaching method is theoretical and contextual, making it difficult for students to understand the material. This article discusses various effective learning strategies to be applied in Civic Education subjects in Elementary Schools. The method used is a literature study with a qualitative descriptive approach. The results of the discussion show that contextual strategies, the use of interactive media, project-based learning, and strengthening local values can have a significant impact on the effectiveness of Civic Education learning. These strategies are considered capable of increasing active student participation, strengthening conceptual understanding, and encouraging internalization of civic values in everyday life.